1970
DOI: 10.1203/00006450-197001000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excess Phenylalanine and of Other Amino Acids on Brain Developmen in the Infant Rat

Abstract: The effects of excess phenylalanine and of a number of other amino acids on brain weight, total brain lipid, and formation of the myelin lipid cerebroside sulfate (sulfatide) have been studied in the newborn rat. Brain weight, amount of brain lipids, and the formation in vivo of sulfatide were reduced as a result of injections of phenylalanine or of certain other amino acids. Total brain cholesterol, cerebroside, and sulfatide were all significantly reduced in phenylalanine-injected animals, although sulfatide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…The present studies thus indi cate that phosphatidylinositol and phosphatidic acid metabolism, as measured by acetate incorporation into their acyl moieties, is not affected by these phenylalanine-loading conditions. Sulfation reactions responsible for sulfatide synthesis are inhibited in suckling rats chronically injected with amino acids [11], No specific effects on sulfatide labeling with acetate were observed in the present acute experi ments. Inhibition of sulfatide labeling also occurs in hypothyroid suckling rats [47], undernourished suckling rats [10] and vitamin A-deficient suckling rats [13,24], The vitamin A deficiency effects were attributed to a secondary undernutrition [24].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The present studies thus indi cate that phosphatidylinositol and phosphatidic acid metabolism, as measured by acetate incorporation into their acyl moieties, is not affected by these phenylalanine-loading conditions. Sulfation reactions responsible for sulfatide synthesis are inhibited in suckling rats chronically injected with amino acids [11], No specific effects on sulfatide labeling with acetate were observed in the present acute experi ments. Inhibition of sulfatide labeling also occurs in hypothyroid suckling rats [47], undernourished suckling rats [10] and vitamin A-deficient suckling rats [13,24], The vitamin A deficiency effects were attributed to a secondary undernutrition [24].…”
Section: Discussionmentioning
confidence: 74%
“…This suggests that ammonia toxicity per se is not the factor causing the reduced acetate uptake into brain in the present experiments. Injections of ammonium carbonate in suckling rats [11] reduced brain growth and radioactive sulfate incorporation into brain sulfatide, indicating that at appropriate dosages ammonium ion can affect brain metabolism. Decreases in acetate incorpora tion did not correlate with brain phenylalanine levels, for 7-day-old brain had levels about two times higher than 2I-day-old brain, while acetate in corporation was depressed somewhat more in 21-day-old brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier investigations have shown that the brain PAPS-forming system can be inhibited by phenylalanine, but not that system from liver [4,5], while kinetic dif ferences have been demonstrated between ATP-sulfurylase and APS-kinase of brain and liver, respectively [6]. Inhibition of PAPS synthesis by phenylalanine in the growing rat brain has been shown by Chase and O'Brien [7]. This inhibition has been localized at ATP-sulfurylase [6].…”
Section: Introductionmentioning
confidence: 90%